Corpus alienum in rectosigmoid: a Case report - Agung Widianto; Wahyu Kartiko Tomo; Fuad Dheni Musthofa; Ghana Hendra (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
A 48-year old man, a referred patient from Wonosobo Hospital, presented to our hospital with severe lower abdomen to anal discomfort since seven days before admission. It is a sudden pain without apparent causes or triggers and accompanied by blood. The patient is uncooperative when asked about the history of inserting objects into the anus and his sexual behaviour. On plain x-rays, a picture of a tubular object in the rectosigmoid region was discovered. After the operation, a foreign body in the form of a Polyvinyl Chloride (PVC) pipe was extracted.